Sexually transmitted infections and the impact on vertical transmission: an integrative review (Research, Society and Development, 2020)
This study aimed to identify the impacts of vertical transmission of sexually transmitted infections in newborns through an integrative review. The methodology was performed from the intersection of the Descriptors in Health Sciences Neonatal Nursing; Sexually transmitted diseases; Infectious Disease Vertical Transmission in the Cumulative Index to Nursing & Allied Health Literature (CINAHL), Scopus, Latin American and Caribbean Health Sciences Literature (LILACS), and Scientific Electronic Library Online (Scielo). At the end of the searches, 29 articles were obtained where 14 of these studies (48.2%) had HIV / AIDS as their central theme. It was found that the need for interruption of breastfeeding, preterm and low birth weight births, neonatal or stillbirth deaths are the main impacts of transmission. It was also identified that infected women should suspend breastfeeding as this may be a source of vertical transmission. In contrast, public policies related to child nutrition prove to be ineffective. Other problems concern the higher prevalence of severe comorbidities, such as pulmonary tuberculosis, bacteremia and diarrheal diseases. From the point of view of the organization of practices related to vertical transmission, comprehensiveness indicates the need for definition by the public power which has competence in the organization of care and therapeutic guidelines. It is concluded that this work opens perspectives for further studies on the aforementioned theme, since effective measures of vertical transmission control are necessary in order to interrupt this cycle that impacts the human development indices of the country.